José Sazbón. Presentación de la antología comentada de su obra - Tocho, Fernanda; Canavese, Mariana; Belforte, María; Starcenbaum, Marcelo; Lvovich, Daniel; Pérez, Alberto Aníbal (2022)
El viernes 01 de julio de 2022 se realizó, en el edificio Sergio Karakachoff de la UNLP, la presentación de los dos volúmenes de la "Antología comentada" de la obra de José Sazbón compilados por Alberto Pérez y Daniel Lvovich. La antología reúne el trabajo realizado durante décadas por el intelectual argentino José Sazbón, quien fuera profesor e investigador de la Facultad de Humanidades y Ciencias de la Educación y el primer Director de la Maestría en Historia y Memoria. Recopilamos aquí las intervenciones de Fernanda Tocho (Secretaria Académica de la Maestría en Historia y Memoria), Mariana Canavese (UBA-CONICET), María Belforte (UBA-CONICET), Marcelo Starcenbaum (UNLP-CONICET), quienes oficiaron de presentadores de la antología, junto a sus compiladores, Daniel Lvovich (UNGS) y Alberto Pérez (UNLP), acompañados además por Carlos Gazzera (Director de Eduvim) y Ayelén Sidún (Decana de la Facultad de Periodismo y Comunicación Social).
On Friday, July 1, 2022, it was held, in the buildingSergio Karakachoff of the UNLP, the presentation of the twovolumes of the "Anthology commented" on the work of José Sazbóncompiled by Alberto Pérez and Daniel Lvovich. The anthologybrings together the work carried out over decades by the intellectualArgentine José Sazbón, who was a professor and researcher at the Faculty of Humanities and Educational Sciences and the first Director of the Master in History and Memory. We collect here the interventions of Fernanda Tocho (Academic Secretary of the Master in History and Memory), Mariana Canavese (UBA-CONICET), María Belforte (UBACONICET), Marcelo Starcenbaum (UNLP-CONICET), who officiated as presenters of the anthology, along withits compilers, Daniel Lvovich (UNGS) and Alberto Pérez (UNLP), also accompanied by Carlos Gazzera (Director of Eduvim) and Ayelén Sidún (Dean of the Faculty of Journalismand Social Communication).
Keywords: José Sazbón; Historia intelectual; Marxismos; Memoria; José Sazbón; Intellectual history; Marxisms; Memory